Longman dictionary of contemporary English (Harlow, 2003)
This dictionary provides 155,000 natural examples that bring English to life, 1 million additional sentences from books and magazines ; has the top 3000 words in spoken and written English highlighted ; 106,000 words and phrases ; 220,000 word combinations that show which words are used together ; a CD-ROM to improve your essay writing, and is quick and easy to use
Keywords: English language,Tiếng Anh